Magnetic particle imaging for assessment of cerebral perfusion and ischemia. (6th October 2021) - Ludewig, Peter; Graeser, Matthias; Forkert, Nils D.; Thieben, Florian; Rández‐Garbayo, Javier; Rieckhoff, Johanna; Lessmann, Katrin; Förger, Fynn; Szwargulski, Patryk; Magnus, Tim; Knopp, Tobias
Abstract: Stroke is one of the leading worldwide causes of death and sustained disability. Rapid and accurate assessment of cerebral perfusion is essential to diagnose and successfully treat stroke patients. Magnetic particle imaging (MPI) is a new technology with the potential to overcome some limitations of established imaging modalities. It is an innovative and radiation‐free imaging technique with high sensitivity, specificity, and superior temporal resolution. MPI enables imaging and diagnosis of stroke and other neurological pathologies such as hemorrhage, tumors, and inflammatory processes. MPI scanners also offer the potential for targeted therapies of these diseases. Due to lower field requirements, MPI scanners can be designed as resistive magnets and employed as mobile devices for bedside imaging. With these advantages, MPI could accelerate and improve the diagnosis and treatment of neurological disorders. This review provides a basic introduction to MPI, discusses its current use for stroke imaging, and addresses future applications, including the potential for clinical implementation. This article is categorized under: Diagnostic Tools > In Vivo Nanodiagnostics and Imaging Therapeutic Approaches and Drug Discovery > Nanomedicine for Neurological Disease Abstract : Magnetic particle imaging is an innovative tomographic imaging technique, which enables point‐of‐care imaging, accurate diagnosis, and treatment of stroke and neurological disorders.